Polemik Gerakan Mentoring Poligami - Latif, Mariana; Fikriana Aulia Raden, Andi Nur (Fakultas Syariah IAI Muhammadiyah Bima, 2022)
This research started from the polemic of polygamy mentoring which became a hot and viral conversation in cyberspace, namely one of the movements that campaigned for polygamy on the basis of a shallow understanding of religion. The method in this research uses two research techniques, namely library research and document research. The primary data in this study were sourced from the Youtube channel Narasi Newsroom: Revealing the Other Side of Paid Polygamy Mentoring and the CokroTV channel: polygamous mentors demeaning women. This research was then analyzed using a descriptive quantitative method. The results showed that the polygamy mentoring movement was a mistake in responding to the permissibility of polygamy in Islamic law and positive law. It was found from what Hafidin said as a polygamous mentor that many men have high libido but are afraid of adultery and wife's permission is not needed in polygamy so this error shows that polygamy places women only as mere lust gratification.